2013
DOI: 10.3844/ajavsp.2013.8.27
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate-Mediated Genomic Changes Involved in Non-Specific Host Defenses, Matrix Remodeling and the Immune Response in the Rumen Epithelium of Cows Afflicted With Subacute Ruminal Acidosis

Abstract: Subacute Ruminal Acidosis (SARA) is a disorder in cattle which can lead to chronic inflammation in the rumen epithelium, known as rumenitis. Butyrate has been shown to attenuate some of the detrimental effects of inflammatory gastroenteral disorders but the molecular mechanisms mediated by butyrate have not been defined. The objective of this study was to define the inflammatory-related genomic changes responsible for the beneficial effects of butyrate. Experimentally, 16 fistulated dairy cows at mid-lactation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 124 publications
3
23
0
Order By: Relevance
“…Indeed, our group has previously reported genomic changes related to cholesterol homeostasis in the rumen of dairy cattle (Steele et al, 2011b). Moreover, we recently reported that major structural changes in the rumen are facilitated by components of the immune system (Dionissopoulos et al, 2013). In order to help better understand the physiological changes that take place during the peripartal period, changes in gene expression of key nutrient metabolic pathways should be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our group has previously reported genomic changes related to cholesterol homeostasis in the rumen of dairy cattle (Steele et al, 2011b). Moreover, we recently reported that major structural changes in the rumen are facilitated by components of the immune system (Dionissopoulos et al, 2013). In order to help better understand the physiological changes that take place during the peripartal period, changes in gene expression of key nutrient metabolic pathways should be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Butyrate concentrations on both days 1 and 7 were higher in butyrate than in control (22.60±0.94 Vs 9.88±0.94 mM and 21.60±0.94 Vs 8.60±0.94 mM; Dionissopoulos et al, 2013). Serum BHBA was higher in the butyrate treatment than the control treatment on both days 1 (4201±265 Vs 910±265 µM) and 7 (3262±265 Vs 800±265 µM; Dionissopoulos et al, 2013).…”
Section: Scfa Blood Rumen Phmentioning
confidence: 99%
“…Butyrate concentrations on both days 1 and 7 were higher in butyrate than in control (22.60±0.94 Vs 9.88±0.94 mM and 21.60±0.94 Vs 8.60±0.94 mM; Dionissopoulos et al, 2013). Serum BHBA was higher in the butyrate treatment than the control treatment on both days 1 (4201±265 Vs 910±265 µM) and 7 (3262±265 Vs 800±265 µM; Dionissopoulos et al, 2013). Rumen pH measurements confirmed the occurrence of acidosis in both butyrate and control treatments, as indicated by the time rumen pH was less than 5.6 (536±89 and 598±97 min/day, respectively; Dionissopoulos et al, 2013).…”
Section: Scfa Blood Rumen Phmentioning
confidence: 99%
See 2 more Smart Citations